2006
DOI: 10.1111/j.1365-3040.2006.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemical stress causes inhibition of growth and oxidative damage in Lycopersicon esculentum Mill

Abstract: The aim of this study was to analyse the effect of allelochemical stress on Lycopersicon esculentum growth. Our results showed that allelochemical stress caused by Sicyos deppei aqueous leachate inhibited root growth but not germination, and produced an imbalance in the oxidative status of cells in both ungerminated seeds and in primary roots. We observed changes in activity of catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD), glutathione reductase (GR) and the plasma membrane NADPH oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 42 publications
5
46
0
2
Order By: Relevance
“…According to the results reached in this work and to those obtained from other studies about the aqueous leachate of Sicyos deppei (Romero-Romero et al, 2005;Lara-Núñez et al, 2006, we provide a more complete understanding of how the compounds present in this extract cause phytotoxicity in tomato germinating seeds, as evidenced through a delay in germination process and radicle growth inhibition.…”
Section: Phytotoxicity Of Sicyos Deppei During Tomato Germinationsupporting
confidence: 67%
See 1 more Smart Citation
“…According to the results reached in this work and to those obtained from other studies about the aqueous leachate of Sicyos deppei (Romero-Romero et al, 2005;Lara-Núñez et al, 2006, we provide a more complete understanding of how the compounds present in this extract cause phytotoxicity in tomato germinating seeds, as evidenced through a delay in germination process and radicle growth inhibition.…”
Section: Phytotoxicity Of Sicyos Deppei During Tomato Germinationsupporting
confidence: 67%
“…We have shown through in vitro assays that watersoluble compounds delay tomato seed germination and inhibit radicle growth. Sicyos deppei phytotoxicity has been associated with diverse metabolic processes, such as the inhibition of the H + -ATPase in the plasma membrane and tonoplast (Romero-Romero et al, 2005), increases in ROS levels, membrane lipid peroxidation, effects on the activity of antioxidant enzymes, and the inhibition of NADPH oxidase activity (Lara-Núñez et al, 2006). Furthermore, the delayed of root protrusion in seeds exposed to S. deppei aqueous leachate has been associated with the reduced activity of cell wall-degrading enzymes, changes in carbohydrate content, and increased levels of abscisic acid (ABA) (Lara-Núñez et al, 2009).…”
mentioning
confidence: 99%
“…Allelopathic potential is an important attribute to the success of an invasive species in natural ecosystems, particularly when the species produces novel biochemical weapons (Callaway & Ridenour 2004). Interactions associated with allelochemicals produced by invasive or native plant species have the potential to impact seed germination, seedling growth, development, and establishment of neighboring plant species, as well as of the same species, in both natural and agricultural systems (Dorning & Cipollini 2006;Lara-Nu´n˜ez et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite well-described overproduction of ROS in tomato plants, observed mainly in short-term reaction to S. deppei leachates, the authors stated that they believe that it is not an oxidative damage responsible for toxicity of the plant (Cruz-Ortega et al 2007), so it is possible that generated ROS may only act as signals activating cascade of other events leading to cell malformations. On the other hand, studies of Lara-Nuñez et al (2006) showed decline inactivity of NADPH oxidase in roots of tomato exposed to leachate of S. deppei. As activity of this enzyme is known to control root development and growth by generation of ROS (Foreman et al 2003), it could be possible that the inhibition of tomato root elongation by allelochemicals of S. deppei might be due to the inhibition of NADPH oxidase, and the subsequent reduction in root ROS level in prolonged treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Water extract from sunflower leaves inhibited seed germination and growth of mustard (Sinapis alba L.) (Oracz et al 2007), due to over-accumulation of ROS, which were not sufficiently scavenged by activated antioxidant enzymatic system (CAT, SOD and glutathione reductase-GR). Allelochemical stress caused by Sicyos deppei G. Don, an invasive annual tendril-bearing vine, endemic to Mexico, was specified by producing an oxidative imbalance evidenced by alteration in ROS generation and modification of antioxidant cellular system in roots of tomato (Solanum lycopersicum L.) (Lara-Nuñez et al 2006;Cruz-Ortega et al 2007). Despite well-described overproduction of ROS in tomato plants, observed mainly in short-term reaction to S. deppei leachates, the authors stated that they believe that it is not an oxidative damage responsible for toxicity of the plant (Cruz-Ortega et al 2007), so it is possible that generated ROS may only act as signals activating cascade of other events leading to cell malformations.…”
Section: Introductionmentioning
confidence: 99%